Correction to: Associations of sphingosine‑1‑phosphate with soluble P‑selectin and adverse clinical outcome in patients with cerebral ischemia with and without acetylsalicylic acid treatment - Nils‑Ole Gloyer; Eileen Moritz; Laura Schwieren; Ulrike Meyer; Götz Thomalla; Günter Daum; Tim Magnus; Rainer Böger; Chi‑un Choe; Bernhard H. Rauch; Edzard Schwedhelm (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Associations of sphingosine-1-phosphate with soluble P-selectin and adverse clinical outcome in patients with cerebral ischemia with and without acetylsalicylic acid treatment - Nils-Ole Gloyer; Eileen Moritz; Laura Schwieren; Ulrike Meyer; Götz Thomalla; Günter Daum; Tim Magnus; Rainer Böger; Chi-un Choe; Bernhard H. Rauch; Edzard Schwedhelm (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)
Patients with overt cerebral ischemia are at risk for adverse events after hospital discharge. Sphingosine-1-phosphate is a potent lipid mediator produced and secreted by platelets, which is inhibited via acetylsalicylic acid (ASA). The associations of sphingosine-1-phosphate with biomarkers of platelet activation, i.e., thromboxane B 2 and soluble P-selectin, as well as with clinical outcome in ischemic stroke or transient ischemic attack patients’ subgroups with and without ASA has not yet been investigated. The bioMARKers in STROKE (MARK-STROKE) cohort is a prospective, single-center, observational study including adult patients with a diagnosis of ischemic stroke or transient ischemic attack. Sphingosine-1-phosphate, thromboxane B 2 , and soluble P-selectin were measured by liquid chromatography-tandem mass spectrometry and ELISA, respectively, to investigate cross-sectional and outcome associations in ASA medication groups. Overall, we included 374 patients (median age 70 (IQR 58; 78) years; sex 242 (64.7%) males; ASA, yes 270 (72.2%)). During the first 365 days of follow-up, we recorded 79 adverse events (death, stroke, myocardial infarction, rehospitalization) in 274 patients with available follow-up. While no statistical differences in neurological and functional deficits were determined by sphingosine-1-phosphate, thromboxane B 2 , and soluble P-selectin in both ASA medication groups, patients without ASA intake and high soluble P-selectin had shorter event-free survival times (high soluble P-selectin 250 (95%CI 205; 296) days; low soluble P-selectin 331 (95%CI 304; 358) days; p = 0.005). In addition, adjusted Cox-regression analysis revealed a higher hazard ratio (HR) for an adverse event during follow-up (HR = 3.22 (95%CI 1.41; 7.36); p = 0.005). Our findings may indicate the usability of soluble P-selectin in ASA-naive patients with ischemic stroke/transient ischemic attack for risk stratification.

Globalism, localism and blue food systems – How can cross-scale tensions be reduced? A production perspective from UK seafood stakeholders - Alex J. Caveen; Bryce D. Stewart; Cameron Moffat; Daniel Skerritt; Estelle Jones; Huw Thomas; Lara Funk; Magnus Johnson; Mike Cohen; Michael Roach; Neil A. Auchterlonie; Samuel Peacock; et al. (Marine Policy, 2025)

Changes in Neuroimmunological Synapses During Cerebral Ischemia - Lynn Bitar; Berta Puig; Thomas G. Oertner; Ádám Dénes; Tim Magnus (Translational Stroke Research, 2025)
The direct interplay between the immune and nervous systems is now well established. Within the brain, these interactions take place between neurons and resident glial cells, i.e., microglia and astrocytes, or infiltrating immune cells, influenced by systemic factors. A special form of physical cell–cell interactions is the so-called “neuroimmunological (NI) synapse.” There is compelling evidence that the same signaling pathways that regulate inflammatory responses to injury or ischemia also play potent roles in brain development, plasticity, and function. Proper synaptic wiring is as important during development as it is during disease states, as it is necessary for activity-dependent refinement of neuronal circuits. Since the process of forming synaptic connections in the brain is highly dynamic, with constant changes in strength and connectivity, the immune component is perfectly suited for the regulatory task as it is in constant turnover. Many cellular and molecular players in this interaction remain to be uncovered, especially in pathological states. In this review, we discuss and propose possible communication hubs between components of the adaptive and innate immune systems and the synaptic element in ischemic stroke pathology.

Measuring riverine macroplastic: Methods, harmonisation, and quality control - Rachel Hurley; Hans Fredrik Veiteberg Braaten; Luca Nizzetto; Eirik Hovland Steindal; Yan Lin; François Clayer; Tim van Emmerik; Nina Tuscano Buenaventura; David Petersen Eidsvoll; Asle Økelsrud; Magnus Norling; Hans Nicolai Adam; et al. (Water Research, 2023)

Unveiling the immunopathology of stroke: a comprehensive view on brain-immune interaction - Tim Magnus; Arthur Liesz (Seminars in Immunopathology, 2023)

The role of the ATP-adenosine axis in ischemic stroke - Ines Sophie Schädlich; Riekje Winzer; Joschi Stabernack; Eva Tolosa; Tim Magnus; Björn Rissiek (Seminars in Immunopathology, 2023)
In ischemic stroke, the primary neuronal injury caused by the disruption of energy supply is further exacerbated by secondary sterile inflammation. The inflammatory cascade is largely initiated by the purine adenosine triphosphate (ATP) which is extensively released to the interstitial space during brain ischemia and functions as an extracellular danger signaling molecule. By engaging P2 receptors, extracellular ATP activates microglia leading to cytokine and chemokine production and subsequent immune cell recruitment from the periphery which further amplifies post-stroke inflammation. The ectonucleotidases CD39 and CD73 shape and balance the inflammatory environment by stepwise degrading extracellular ATP to adenosine which itself has neuroprotective and anti-inflammatory signaling properties. The neuroprotective effects of adenosine are mainly mediated through A 1 receptors and inhibition of glutamatergic excitotoxicity, while the anti-inflammatory capacities of adenosine have been primarily attributed to A 2A receptor activation on infiltrating immune cells in the subacute phase after stroke. In this review, we summarize the current state of knowledge on the ATP-adenosine axis in ischemic stroke, discuss contradictory results, and point out potential pitfalls towards translating therapeutic approaches from rodent stroke models to human patients.

The Bep gene cluster in Burkholderia cenocepacia H111 codes for a water-insoluble exopolysaccharide essential for biofilm formation - Barbara Bellich; Lucrecia C. Terán; Magnus M. Fazli; Francesco Berti; Roberto Rizzo; Tim Tolker-Nielsen; Paola Cescutti (Carbohydrate Polymers, 2023)

Interleukin-1 Mediates Ischemic Brain Injury via Induction of IL-17A in γδ T Cells and CXCL1 in Astrocytes - Ines Sophie Schädlich; Jonas Heinrich Vienhues; Alina Jander; Marius Piepke; Tim Magnus; Kate Lykke Lambertsen; Bettina Hjelm Clausen; Mathias Gelderblom (NeuroMolecular Medicine, 2022)
As a prototypical proinflammatory cytokine, interleukin-1 (IL-1) exacerbates the early post-stroke inflammation, whereas its neutralization is protective. To further investigate the underlying cell-type-specific IL-1 effects, we subjected IL-1 (α/β) knockout ( Il1 −/− ) and wildtype (WT) littermate mice to permanent middle cerebral artery occlusion (pMCAO) and assessed immune cell infiltration and cytokine production in the ischemic hemisphere by flow cytometry 24 h and 72 h after stroke. Il1 −/− mice showed smaller infarcts and reduced neutrophil infiltration into the ischemic brain. We identified γδ T cells and astrocytes as target cells of IL-1 signaling-mediated neutrophil recruitment. First, IL-1-induced IL-17A production in γδ T cells in vivo , and IL-17A enhanced the expression of the main neutrophil attracting chemokine CXCL1 by astrocytes in the presence of tumor necrosis factor (TNF) in vitro. Second, IL-1 itself was a potent activator of astrocytic CXCL1 production in vitro. By employing a novel FACS sorting strategy for the acute isolation of astrocytes from ischemic brains, we confirmed that IL-1 is pivotal for Cxcl1 upregulation in astrocytes in vivo. Our results underscore the pleiotropic effects of IL-1 on immune and non-immune cells within the CNS to mount and amplify the post-stroke inflammatory response.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Niche and neutral assembly mechanisms contribute to latitudinal diversity gradients in reef fishes - Nestor E. Bosch; Thomas Wernberg; Tim J. Langlois; Dan A. Smale; Pippa J. Moore; João N. Franco; Pierre Thiriet; Eric Feunteun; Cláudia Ribeiro; Pedro Neves; Rui Freitas; Karen Filbee‐Dexter; et al. (Journal of Biogeography, 2021)
Aim The influence of niche and neutral mechanisms on the assembly of ecological communities have long been debated. However, we still have a limited knowledge on their relative importance to explain patterns of diversity across latitudinal gradients (LDG). Here, we investigate the extent to which these ecological mechanisms contribute to the LDG of reef fishes. Location Eastern Atlantic Ocean. Taxon Reef‐associated ray‐finned fishes. Methods We combined abundance data across ~60° of latitude with functional trait data and phylogenetic trees. A null model approach was used to decouple the influence of taxonomic diversity (TD) on functional (FD) and phylogenetic (PD) diversity. Standardized effect sizes (SES FD and SES PD) were used to explore patterns of overdispersion, clustering and randomness. Information theoretic approaches were used to investigate the role of large‐ (temperature, geographic isolation, nitrate and net primary productivity) and local‐scale (human population and depth) drivers. We further assessed the role of demographic stochasticity and its interaction with species trophic identity and dispersal capacity. Results Taxonomic diversity peaked at ~15°–20°N, with a second mode of lower magnitude at ~45°N; a pattern that was predicted by temperature, geographic isolation and productivity. Tropical regions displayed a higher proportion of overdispersed assemblages, whilst clustering increased towards temperate regions. Phylogenetic and functional overdispersion were associated with warmer, productive and isolated regions. Demographic stochasticity also contributed largely to community assembly, independently of ecoregions, although variation was dependent on the trophic identity and body size of species. Main conclusions Niche‐based processes linking thermal and resource constraints to local coexistence mechanisms have contributed to the LDG in reef fishes. These processes do not act in isolation, stressing the importance of understanding interactions between deterministic and stochastic factors driving community structure in the face of rapid biodiversity change.

Intravenous Immunoglobulin (IVIg) Induce a Protective Phenotype in Microglia Preventing Neuronal Cell Death in Ischaemic Stroke - Vivien Häußler; Tristan Daehn; Björn Rissiek; Vanessa Roth; Christian Gerloff; Thiruma V. Arumugam; Tim Magnus; Mathias Gelderblom (NeuroMolecular Medicine, 2020)

Extra-pair paternity and sperm length variation in the socially monogamous Fieldfare Turdus pilaris - Oddmund Kleven; Aksel N. Fiske; Magnus Håvik; Rolf T. Kroglund; Jan E. Østnes; Tim Schmoll (Journal of Ornithology, 2019)

Shelf–Basin interaction along the East Siberian Sea - Leif G. Anderson; Göran Björk; Ola Holby; Sara Jutterström; Carl Magnus Mörth; Matt O'Regan; Christof Pearce; Igor Semiletov; Christian Stranne; Tim Stöven; Toste Tanhua; Adam Ulfsbo; et al. (Ocean Science, 2017)
Extensive biogeochemical transformation of organic matter takes place in the shallow continental shelf seas of Siberia. This, in combination with brine production from sea-ice formation, results in cold bottom waters with relatively high salinity and nutrient concentrations, as well as low oxygen and pH levels. Data from the SWERUS-C3 expedition with icebreaker Oden, from July to September 2014, show the distribution of such nutrient-rich, cold bottom waters along the continental margin from about 140 to 180° E. The water with maximum nutrient concentration, classically named the upper halocline, is absent over the Lomonosov Ridge at 140° E, while it appears in the Makarov Basin at 150° E and intensifies further eastwards. At the intercept between the Mendeleev Ridge and the East Siberian continental shelf slope, the nutrient maximum is still intense, but distributed across a larger depth interval. The nutrient-rich water is found here at salinities of up to ∼ 34.5, i.e. in the water classically named lower halocline. East of 170° E transient tracers show significantly less ventilated waters below about 150 m water depth. This likely results from a local isolation of waters over the Chukchi Abyssal Plain as the boundary current from the west is steered away from this area by the bathymetry of the Mendeleev Ridge. The water with salinities of ∼ 34.5 has high nutrients and low oxygen concentrations as well as low pH, typically indicating decay of organic matter. A deficit in nitrate relative to phosphate suggests that this process partly occurs under hypoxia. We conclude that the high nutrient water with salinity ∼ 34.5 are formed on the shelf slope in the Mendeleev Ridge region from interior basin water that is trapped for enough time to attain its signature through interaction with the sediment.

Masked, diluted and drowned out: how global seafood trade weakens signals from marine ecosystems - Beatrice I Crona; Tim M Daw; Wilf Swartz; Albert V Norström; Magnus Nyström; Matilda Thyresson; Carl Folke; Jonas Hentati‐Sundberg; Henrik Österblom; Lisa Deutsch; Max Troell (Fish and Fisheries, 2016)
Nearly 40% of seafood is traded internationally and an even bigger proportion is affected by international trade, yet scholarship on marine fisheries has focused on global trends in stocks and catches, or on dynamics of individual fisheries, with limited attention to the link between individual fisheries, global trade and distant consumers. This paper examines the usefulness of fish price as a feedback signal to consumers about the state of fisheries and marine ecosystems. We suggest that the current nature of fisheries systems and global markets prevent transmission of such price signals from source fisheries to consumers. We propose several mechanisms that combine to weaken price signals, and present one example – the N orth S ea cod – to show how these mechanisms can be tested. The lack of a reliable price feedback to consumers represents a challenge for sustainable fisheries governance. We therefore propose three complimentary approaches to address the missing feedback: (i) strengthening information flow through improved traceability and visibility of individual fishers to consumers, (ii) capitalizing on the changing seafood trade structures and (iii) bypassing and complementing market mechanisms by directly targeting citizens and political actors regarding marine environmental issues through publicity and information campaigns. These strategies each have limitations and thus need to be pursued together to address the challenge of sustainability in global marine fisheries.

C5a Receptor (CD88) Inhibition Improves Hypothermia-Induced Neuroprotection in an In Vitro Ischemic Model - John Thundyil; Dale Pavlovski; Yu-Hsuan Hsieh; Mathias Gelderblom; Tim Magnus; David P. Fairlie; Thiruma V. Arumugam (NeuroMolecular Medicine, 2012)

Impaired hatching success and male-biased embryo mortality in Tree Sparrows - Magnus Svensson; Pekka T. Rintamäki; Tim R. Birkhead; Simon C. Griffith; Arne Lundberg (Journal of Ornithology, 2007)